Penampilan Produksi Sapi PO dan PFH Jantan yang Mendapat Pakan Konsentrat dan ”Hay” Rumput Gajah - R Adiwinarti; I P Kusuma; C M Sri Lestari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2010)
This research has been done during August 2004 - January 2005 at Laboratorium Ilmu Ternak Potong dan Kerja, Fakultas Peternakan Universitas Diponegoro Semarang. The study was set up to investigate the performance of ongole crossbred and Friesian Holstein crossbred young bulls fed concentrate and Napier grass hay. This research used 4 yearling ongole crossbred (PO) bulls with the initial body weight: 228,17 + 14,77 kg (CV = 6,47%) and 4 yearling friesian holstein crossbred (PFH) bulls with the body weight: 196,34 + 7,64 kg (CV = 3,89%). The Independent Sample Comparisons was used in this study. Those bulls were fed 30% hay of Napier grass and 70% concentrate made of “bungkil kelapa sawit” (80%) and rice bran (20%). The ration was given based on dry matter need, 2.5% of the body weight. Parameters observed were the average daily gain (ADG), feed intake (dry matter intake, crude protein intake, Total Digestible Nutrients’ 2 Sains Peternakan Vol.8 (1), Maret 2010 intake) and feed conversion. Data were analyzed using t-test; except for feed conversion was analyzed deskriptifely.The result indicated that those cattle fed concentrate and Napier grass had ADG and feed intake relatively similar. The average of ADG PO bulls were 0.21 kg and PFH bulls were 0.22 kg. Dry matter intakes of PO and PFH bulls were 3.33 kg/day and 2.83 kg/day. Crude protein intake of PO bulls were 0,45 kg/day and that of PFH bulls were 0,38 kg/day, whereas TDN intake of PO bulls were 1,93 kg/day and PFH bulls were 1,20 kg/day. Feed conversion of PO bulls was 15.86 and that of PFH bulls was 12.86. It can be concluded that the performance of Ongole crossbred and Friesian Holstein crossbred young bulls fed concentrate and Napier grass hay was similar. Those indicated that PFH bulls had productivity that was the same as PO bulls. Key words : Bulls, performance, feed intake, feed conversion